Clowning around stories, facts, puzzles, poems, fun! - Ellis, Julie; Bacon, Helen; Shortland Publications (Auckland, New Zealand Shortland Publications, 2003)
A multifaceted book combining engaging stories, intriguing facts, interactive puzzles, and delightful poems, all themed around clowns, designed to entertain and educate young readers.
Includes a collection of stories, factual information, puzzles, and poems centered around the theme of clowns.
Suitable for children aged 7-10 years.
Keywords: Clowns